Cooperative Adaptations and Evolution in Plant-Microbe Systems - Tatiana Matveeva (Frontiers Research Topics, 2018)
Ecological and evolutionary genetics of plant-microbe interactions is of high importance for developing the plant science since the plants originated symbiotically (via incorporation of a phototrophic cyanobacterium into a heterotrophic eukaryon) and further evolve as the multipartite symbiotic systems, harboring the enormously diverse microbial communities. The Research Topic has integrated the top-level research on the genetic interactions in the plant-microbial associations required to develop the novel evolutionary approaches in the molecular and ecological genetics of different kinds of symbioses.